PENGARUH PENGETAHUAN INVESTASI DAN MOTIVASI INVESTASI TERHADAP MINAT MAHASISWA BERINVESTASI SAHAM DI PASAR MODAL: (Studi pada mahasiswa Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Maluku) - Angel Merlyn Pattimahu (Jurnal Administrasi Terapan, 2023)
This study aims to: (1) Determine the effect of investment knowledge on investment interest in the capital market for students of the UKIM economics faculty. (2) Knowing the effect of investment motivation on interest in investing in the capital market in economics faculty UKIM students. The research design is quantitative. The population in this study were students of the UKIM Faculty of Economics. The sample in this study were 83 students. Collecting data in this study using a questionnaire method. The test instruments were analyzed using validity, reliability, normality tests,. The data analysis technique used in this research is descriptive statistics, multiple linear regression analysis and the results of hypothesis testing. The results of this study indicate that: (1) Knowledge of investment has an effect on the interest in investing in the capital market for FE UKIM students, as evidenced by a probability value of 0.000 <0.05. (2) Investment motivation affects the interest in investing in the capital market for FE UKIM students as evidenced by a probability value of 0.000 <0.05. (3) Knowledge and investment motivation simultaneously affect the interest in investing in the capital market for FE UKIM students, as evidenced by the Fcount of 100.448 and a probability of 0.000. (4) Independent variables jointly affect the dependent variable by 70.8%, the remaining 29.2% is influenced by other variables. Keywords: investment knowledge, investment motivation, investment interest in the capital mar